Relationship Banking and Its Role in Corporate Governance - Sang-woo Nam (Asian Development Bank Institute (ADBI), 2004)
Bank-based systems of corporate governance are certainly an alternative in many Asian economies. In spite of the great efforts directed to strengthening corporate governance along the Anglo- American model in recent years, the effectiveness of this model is far from being clear. Among other things, it requires many strong market and regulatory institutions to support it, and this is a challenging task for these economies. The bank-based model has advantages in this and other respects. Banks with a stable long-term relationship with their corporate clients are considered to have an important corporate governance role, particularly when the firms face deteriorations in their performance. This paper reviews theoretical and empirical literature on relationship banking to evaluate its advantages and risks, evaluates the constraints to fostering relationship banking in Asian economies, and presents the result of a questionnaire survey conducted in Korea's major commercial banks in order to assess the perceptions of bankers on relationship banking and bank governance. An extensive review of the empirical literature shows that relationship banking can make a valuable contribution to the economy by allowing for the efficient monitoring of corporate borrowers, reducing information asymmetry that is an essential element of imperfection in financial markets. As a result, firms with a relationship bank tend to have easier access to credit, be less liquidity-constrained in their business activities, and receive assistance more readily from the bank when they are in financial distress. Relationship banks can play an important corporate governance role as they typically intervene in corporate management at the first signs of performance deterioration. This practice of contingent corporate governance can provide a flexible, informal alternative to the market for corporate control or bankruptcy proceedings. Relationship banking has risks as well: corporate risk-taking may be discouraged, constraining growth potential; firms may be informationally captured by their banks and pay monopoly rents; and banks may face serious conflicts of interests when their clients fall into financial distress. The empirical evidence is often mixed; this seems to a large extent to be attributable to the difficulty in defining relationship banking. Banks in the Asian economies have been and are still considered to be constrained in terms of developing relationship banking. Given poor governance in the banks, which themselves are under the control of families or the government, connection-based lending rather than relationship banking has been prevalent. Deregulation and increased competition in the financial markets may pose a threat to relationship banking, though this is not necessarily the case once the relationship is already established or when progress is made toward a universal banking system. Relationship banking also comes under stress in times of serious financial distress for either banks or their client firms. The banks face the risks of being accused of abusing conflicts of interests or neglecting their expected obligations as relationship banks. Financial trouble and the consequent exit of a relationship bank, especially in an economy-wide crisis, is not only a fatal blow to the client firms but also a loss of the information capital held by the bank.
hdl:11540/4161
Keywords: 330; Bankgeschäft; Kreditgeschäft; Corporate Governance; Welt; Asien; Südkorea